Adolescent mice exhibit lower reward sensitivity than adults - Misiołek, Klaudia; Chrószcz, Magdalena; Klimczak, Marta; Rzeszut, Aleksandra; Netczuk, Julia; Ziółkowska, Barbara; Szumiec, Łukasz; Kaczmarczyk-Jarosz, Maria; Harda, Zofia; Rodriguez Parkitna, Jan (Frontiers in Behavioral Neuroscience, 2025)
IntroductionAdolescence shapes adaptive adult behaviors. It is characterized by increased responsiveness to socially salient stimuli and heightened sensitivity to rewards in peer settings. The particular importance of social context during adolescence indicates that neural circuits responsible for social reward may develop along a different trajectory from those involved in non-social reward processing. However, this remains largely unexplored, as much of the existing research tends to focus on a single reward type, a specific age group of adolescents, or a single sex, thereby limiting a comprehensive understanding of how reward processing evolves across development.MethodsHere, we investigated how social, cocaine, and palatable food reward sensitivity is expressed in female and male C57BL/6 mice across early- (pubertal onset), mid- (peripubertal phase), and late- (sexual maturity) adolescence, compared to adults. We examined how these different rewards become associated with environmental contexts across developmental stages using the conditioned place preference (CPP) paradigm, a fundamental method for evaluating the motivational properties of stimuli.ResultsWe found that adolescent mice exhibited a lower preference for social and palatable food conditioned contexts, while cocaine CPP was not significantly affected by age. Comparisons across CPP tasks confirmed that age, rather than reward type or sex, was the primary factor influencing the magnitude of CPP. Overall, mid- and late-adolescent mice showed reduced mean CPP, with mid-adolescents exhibiting significantly lower odds of expressing a conditioned preference relative to adults.DiscussionThese findings challenge the prevailing assumption that adolescent reward sensitivity universally enhances reward-context learning. Instead, we propose that the attenuated CPP observed in adolescence reflects lower reward sensitivity in emotionally neutral conditions, rather than deficits in associative learning or increased novelty seeking. Our results highlight how developmental stage influences reward-related behaviors and underscore the need for age- and sex-specific analyses in behavioral studies.